Determining the mode characteristics of voltage regulator with capacitive load - Fediv, Yevhen; Sivakova, Olha (Eastern-European Journal of Enterprise Technologies, 2022)
The tasks of dynamic compensation of reactive power are solved by means of flexible AC transmission systems using power electronics devices. The object of this study is a variable voltage regulator with a capacitive load. This paper considered the problem of the efficiency of phase voltage regulation on the capacitor battery to use it as a source to compensate for reactive power. The results of the study are presented, which justify the effectiveness of the technique for obtaining a dynamic source of reactive power based on the use of a thyristor voltage regulator with a capacitive load. A comparative study of two regimes of the regulator was carried out: the phase-controlled mode of closing fully controlled semiconductor gates and the phase-controlled mode for opening single-core semiconductor gates. Analytical expressions for angular characteristics of power according to the main harmonics are derived. It is shown that under the first mode the current through the capacitor is capacitive, which makes it possible to obtain a thyristor-adjustable capacitor battery for dynamic compensation of reactive power in power supply systems. It was found that under the second mode, simultaneously with the regulation of reactive power, there is a phenomenon of consumption from the active power supply network according to the main harmonics. This means that the regulation of current through an ideal capacity using ideal phase-controlled semiconductor gates is accompanied by the consumption of the active component of the current from the power supply network. The resulting component of active power in the electrical circuit without active resistances is proposed to be called "active artificial shear power". The results have been confirmed by studies on virtual models